2018
DOI: 10.5032/jae.2018.02179
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Learning Opportunities in Agriculture, Food, Natural Resources, and Science: The Role of the Teacher

Abstract: Providing interdisciplinary learning opportunities in agriculture, food, natural resources (AFNR), and science is critically important. School-based agricultural education offers a valuable platform to connect AFNR and science; however, interdisciplinary teaching requires willing and able teachers. The current study considered the intentions of school-based agriculture teachers to teach science within AFNR curriculum. Using the theory of planned behavior, attitude toward teaching science, subjective norms, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Although differences exist in how the connection between AFNR and science is framed, there is agreement in the value of learning experiences which illuminate the relationship between AFNR and science (McKim, Velez, Lambert, & Balschweid, 2017). As an example, learning experiences which connect AFNR and science can empower students to identify, investigate, and implement solutions to agricultural practices which damage the environment (McKim, Pauley, Velez, & Sorensen, 2018).…”
Section: Interdisciplinarymentioning
confidence: 99%
See 1 more Smart Citation
“…Although differences exist in how the connection between AFNR and science is framed, there is agreement in the value of learning experiences which illuminate the relationship between AFNR and science (McKim, Velez, Lambert, & Balschweid, 2017). As an example, learning experiences which connect AFNR and science can empower students to identify, investigate, and implement solutions to agricultural practices which damage the environment (McKim, Pauley, Velez, & Sorensen, 2018).…”
Section: Interdisciplinarymentioning
confidence: 99%
“…Two studies were identified which address the degree AFNR educators intended to teach science within their curriculum. A study by McKim et al (2018) identified AFNR educators intended to include science concepts and practices in nearly 40% of the total curriculum, though intentions ranged across pathways from 18% in agribusiness systems to 57% in plant systems. Specific to the relationship between science teaching intentions and CASE, Carraway, Ulmer, Burris, and Irlbeck (2015) identified overwhelming intentions of preservice AFNR educators to teach science with CASE curriculum after completion of a semester-long CASE certification course.…”
Section: Science Teaching Intentionsmentioning
confidence: 99%
“…Throughout the development of the project, students learn to select the relevant information for their training and integrate it with the dynamics of their professional future. AMs generate student independence in seeking out this information, thereby improving performance in the classroom [8,31]. AM teaching can make it possible to engage the student in their educational formation, in this case, regarding knowledge of soil microbiology and inoculant subjects and their applications to agriculture or environmental science [8].…”
Section: Discussionmentioning
confidence: 99%
“…They advocated beginning in K-12 education. However, there is a paucity of research on interdisciplinary teaching in K-12 agricultural education (McKim et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Resources and references appropriate for high school agricultural education were not found. As noted by McKim, Pauley, Velez, and Sorensen (2018), "SBAE [School-Based Agricultural Education] research has failed to provide a comprehensive, empirical model detailing the role of the teacher in facilitating interdisciplinary science and AFNR [Agriculture, Food, and Natural Resources] learning" (p. 179). Given the paucity of research in this area, the purpose of this study was to explore student reactions being taught with an interdisciplinary teaching method in a secondary agricultural education context.…”
Section: Introductionmentioning
confidence: 99%